ETIKA KOMUNIKASI KONSELOR DALAM KONSELING ONLINE BERBASIS TEKS - Sheilla, Ainun; Budiman, Nandang; Nadhirah, Nadia Aulia (JKP (Jurnal Konseling Pendidikan), 2023)
In addition to the various advantages of text-based online counseling, there are several factors that can hinder its implementation. Some of these factors include punctuation and emoji errors; Inappropriate wording or font use; delays in replying to messages; and not using good, polite, and clear language. This article aims to examine how counselor communication ethics in implementing text-based online counseling services. The research in this article uses a literature review method with a qualitative descriptive approach. There is no guideline/code of ethics that specifically addresses text-based online counseling. Therefore, when carrying out text-based online counseling, each counselor has their own strategy, according to their experience, competence, and skills. A counselor in providing online counseling services must have a foundation of technology-related competencies and competencies related to text-based counseling itself. The skills that must be possessed in conducting text-based online counseling are typing skills, typing style, and how to attitude in writing.